2022
DOI: 10.1177/14644207221081951
|View full text |Cite
|
Sign up to set email alerts
|

Dissimilar joining of Titanium alloy to Aluminium using Al-Si based filler alloy by vacuum brazing technique

Abstract: In the present investigation, a dissimilar metal joint between Titanium alloy (Ti6Al4V, ELI) and pure Aluminium (Al) was achieved using an Al-Si based filler alloy by vacuum brazing technique. A sound dissimilar joint of Ti to Al was achieved after a series of pilot experiments with overlap configuration. A thin foil of 0.2 mm thick Al-Si was used as filler alloy. With an overlap of 7.5 mm, the average joint strength achieved was 64 MPa. Mechanical properties were evaluated by varying the overlaps of the vacuu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…( ) 00 sin 2 us P P f t t P  =  − +    (12) According to Equation (12), it could be concluded that the sound pressure gradient changed with time, so it could explain why the liquid solder had an instantaneous process of repeated forward and contraction motion during the CF process. According to Equation (10), it could be concluded that if the liquid layer moved in the X direction, the sound pressure gradient satisfied the following equation:…”
Section: Interface Mechanical Analysis Of Liquid Solder Cf Processmentioning
confidence: 99%
See 1 more Smart Citation
“…( ) 00 sin 2 us P P f t t P  =  − +    (12) According to Equation (12), it could be concluded that the sound pressure gradient changed with time, so it could explain why the liquid solder had an instantaneous process of repeated forward and contraction motion during the CF process. According to Equation (10), it could be concluded that if the liquid layer moved in the X direction, the sound pressure gradient satisfied the following equation:…”
Section: Interface Mechanical Analysis Of Liquid Solder Cf Processmentioning
confidence: 99%
“…Vacuum brazing is a welding method in which the brazing filler metal is melted by heating in a vacuum or inert gas environment, so that it penetrates into the surface of the base metal and solidifies, and finally forms a solid connection. Due to the advantages of high quality and strong corrosion resistance, the welded joints prepared by this method have received extensive attention in recent years [9,10]. Ma et al [11] inserted a 3D-SiO2 fiber interlayer between SiC and TC4 alloy (with a nominal composition of Ti-6Al-4V), and then performed vacuum brazing.…”
Section: Introductionmentioning
confidence: 99%